الحرية السياسية للموظف العام في التشريع الجزائري - عليان, عبد الغاني (جامعة الوادي.University eloued, 2021)
الموظف العام مثل أي مواطن يستطيع ممارسة الحقوق والحريات السياسية التي تكفلها له الدساتير والقوانين النافذة في هذا الشأن ، الأمر الذي جعل دراسة موضوع ممارسة الموظف العام للحريات السياسية في غاية الأهمية والشائكة في الدولة. في الوقت نفسه ، لأن هذا لا ينعكس فقط على الحياة المهنية للموظفين العموميين ، ولكن أيضًا على الحياة السياسية للمجتمع بأسره ، الأمر الذي يتطلب التوفيق بين ضرورة تمتعهم بممارسة الحرية السياسية التي يكفلها الدستور لجميع المواطنين. والواقع أن وضع الموظف العام قد تطور فيما يتعلق بممارسة الحقوق والحريات السياسية. وقد اشتهر بإبداء رأيه في الأمور العامة، وكذلك مشاركته في الانتخابات سواء كناخب أو منتخب، وكذلك تكوين نقابات وظيفية والانضمام إلى الأحزاب السياسية بعد حرمانه من ذلك، ولكن ممارسة هذه الحقوق لها إطار وضوابط يجب ممارستها من أجل التمتع بالحقوق والحريات السياسية للموظف. The public servant is like any citizen who can exercise the rights and political freedoms guaranteed to him by the constitutions and laws in force in this regard, which made the study of the subject of the public servant’s exercise of political freedoms extremely important and thorny at the same time, as this reflects not only on the career life of public officials, but also The political life of the whole society, which requires reconciliation between the necessity of their enjoyment of the exercise of political freedom guaranteed by the Constitution to all citizens. In fact, the situation of the public servant has evolved regarding the exercise of political rights and freedoms. He has been recognized for expressing his opinion in public matters, as well as participating in elections, whether as an elector or elected, as well as forming functional unions and joining political parties after he was deprived of that, but the practice of these Rights have a framework and controls that must be exercised in order to enjoy the rights and political freedoms of the employee.
قانون اداري
Keywords: الموظف العام ،الحقوق والحريات; The public servant ،political freedom guaranteed